A place at the table is not enough: Accountability for Indigenous Peoples and local communities in multi-stakeholder platforms. (July 2022) - Larson, Anne M.; Sarmiento Barletti, Juan Pablo; Heise Vigil, Nicole
Highlights: Virtually all global efforts aimed at more sustainable land- and resource-use practices call for multi-stakeholder process. Surprisingly little attention has been given to IPLC perspectives on multi-stakeholder forums, and even less so comparatively across cases. Most of the MSFs studied show they have not learned much from past experience, research and lessons on "invited spaces". IPLC interviewees were mostly optimistic about the potential of MSFs, but their answers revealed accountability failures. Thinking strategically about participation and separate organizing spaces can facilitate construction of counterpower. Abstract: Virtually all major efforts to address global problems regarding land and resource use call for a multi-stakeholder process. At the same time, there is growing interest in, and commitment to, inclusion of previously marginalized groups – e.g., Indigenous Peoples and local communities (IPLCs), smallholders, and women in these groups – in decisions related to sustainable land and resource governance. Nevertheless, multi-stakeholder platforms and forums (MSFs) tend to be idealized as imagined spaces for collaboration among equals, despite ample prior research demonstrating that fostering equity in such "invited spaces" is no easy feat. This article draws on a comparative study of 11 subnational MSFs aimed at improving land and forest use practices in Brazil, Ethiopia, Indonesia and Peru. It analyzes data from interviews with more than 50 IPLC forum participants to understand their perspective on efforts to address equity in the MSFs in which they are participating, as well as their opinion of the potential of MSFs in comparison with other participants. The research sought to understand how MSFs can ensure voice and empowerment and address inequality, and thus be accountable to the needs and interests of IPLCs. The interviews show that IPLCs are overall optimistic, but the results also provide insights into accountability failures. The article argues that to bring about change – one that takes equality, empowerment and justice seriously – there needs to be greater strategic attention to how marginalized groups perceive their participation in multi-stakeholder processes. It builds on the lessons from the literature and the findings to propose specific ways that MSFs might foster the collective action or counter power that less powerful actors need to hold more powerful actors accountable.